Conversation as method : analyzing the relational world of people who were raised communally - Josselson, Ruthellen (Sage Publications, 1997)
Conversation as Method is a most unique and engaging discussion among four women, all feminist scholars, who explore the different ways of knowing. The quantitative orientation of one combined with the qualitative methodology of the other three makes for stimulating development of interview and exchange on how growing up communally affects relationships later on in life. All four authors have worked, independently, on issues relative to the kibbutz experience, and each brings her own perspective to this dialogue and to the active pursuit of data gathering and understanding. From the premise that knowledge is co-constructed by observer and observed and both must be clearly visible in research reports, Conversation as Method is rich social science evolving from people coming together to talk, listen, and learn from one another. Readers are also encouraged to participate in the conversation by making their own individual assessments of interpretations each author puts forth.